2003
DOI: 10.1002/fld.478
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of unsteady turbulent flows around oscillating and ramping aerofoils

Abstract: SUMMARYThe aim of this work is to computationally investigate subsonic and transonic turbulent ows around oscillating and ramping aerofoils under dynamic-stall conditions. The investigation is based on a highresolution Godunov-type method and several turbulence closures. The Navier-Stokes and turbulence transport equations are solved in a strongly coupled fashion via an implicit-unfactored scheme. We present results from several computations of ows around oscillating and ramping aerofoils at various conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…A complete review on the numerical simulations of dynamic stall [14][15][16][17][18][19][20] can be found in the work of Ekaterinaris and Platzer. 21 One of the major outcomes of this survey is a list of research topics that required further advancements for achieving reliable predictions.…”
Section: -2mentioning
confidence: 99%
“…A complete review on the numerical simulations of dynamic stall [14][15][16][17][18][19][20] can be found in the work of Ekaterinaris and Platzer. 21 One of the major outcomes of this survey is a list of research topics that required further advancements for achieving reliable predictions.…”
Section: -2mentioning
confidence: 99%
“…Many experiments and CFD calculations have been performed on the flow around airfoils forced to oscillate in different kinds of motions (Barakos and Drikakis, 2003;Maresca, Favier and Rebont, 1979;Piziali, 1994;Pascazio et al, 1996;Favier et al, 1988), including ramping, translation, pitching, plunging, and combined motion in either pitching-plunging or translation-pitching. However, very few experiments have been dedicated to the characterization of the flow close to the moving wall and within the boundary layer region.…”
Section: Steady/unsteady Flows Around Airfoils and Cylindersmentioning
confidence: 99%
“…At the beginning, the compressibility effect was neglected due to limitation of the computational time (Fung and Carr 1991). This problem was brought up again to the surface in the late of '90s by considering the compressibility and turbulence model influences (Ekaterinaris 1995;Ekaterinaris et al 1995;Barakos and Drikakis 2003). However, due to the lack of robust CFD methods, most CFD works were done only focusing on the validation of the CFD codes rather than the physical phenomena of the flow.…”
Section: Introductionmentioning
confidence: 99%
“…Past studies on turbulent flow have shown that the accuracy of numerical predictions is signicantly affected by the accuracy of the employed turbulence model (Barakos and Drikakis 2003). The zeroequation turbulence model was shown to inaccurately predict separated flow by Baldwin and Lo-max (Baldwin and Lomax 1978).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation